2016
DOI: 10.5951/jresematheduc.47.3.0206
|View full text |Cite
|
Sign up to set email alerts
|

Improving Mathematics Learning of Kindergarten Students Through Computer-Assisted Instruction

Abstract: This study evaluated the effects of a mathematics software program, the Building Blocks software suite, on young children's mathematics performance. Participants included 247 Kindergartners from 37 classrooms in 9 schools located in low-income communities. Children within classrooms were randomly assigned to receive 21 weeks of computer-assisted instruction (CAI) in mathematics with Building Blocks or in literacy with Earobics Step 1. Children in the Building Blocks condition evidenced higher posttest scores o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…For example, Schacter et al (2016) found that playing math games based on Montessori activities on a tablet for 10 minutes a day three times a week for 6 weeks significantly improved prekindergartners' performance on early number tasks. In the study most similar to the present one in terms of participants, sample size, and duration, Foster et al (2016) conducted a randomized controlled trial of 21 weeks of computer-assisted instruction for 247 kindergartners in nine schools in low-income communities and found significant improvements in early numeracy and applied problems in the treatment group. Similarly, studies of digital applications provided along with curricula like Building Blocks (Clements & Sarama, 2007) or Big Math for Little Kids (Greenes et al, 2004) have found that applications designed by the research team and implemented as part of the curriculum have led to learning gains.…”
Section: Literature Reviewmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, Schacter et al (2016) found that playing math games based on Montessori activities on a tablet for 10 minutes a day three times a week for 6 weeks significantly improved prekindergartners' performance on early number tasks. In the study most similar to the present one in terms of participants, sample size, and duration, Foster et al (2016) conducted a randomized controlled trial of 21 weeks of computer-assisted instruction for 247 kindergartners in nine schools in low-income communities and found significant improvements in early numeracy and applied problems in the treatment group. Similarly, studies of digital applications provided along with curricula like Building Blocks (Clements & Sarama, 2007) or Big Math for Little Kids (Greenes et al, 2004) have found that applications designed by the research team and implemented as part of the curriculum have led to learning gains.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Studies on technology in early childhood have shown that children and teachers enjoy using technological tools (Blackwell, 2014;Brown, 1992), but research has not yet provided clear evidence about how these tools can impact learning (Blackwell, 2014;Dynarski et al, 2007;Flewitt et al, 2015). Some studies have found that well-designed applications can positively impact mathematics learning (Foster et al, 2016;Wu et al, 2012). For example, Schacter et al (2016) found that playing math games based on Montessori activities on a tablet for 10 minutes a day three times a week for 6 weeks significantly improved prekindergartners' performance on early number tasks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Annual standardized assessments have become the predominant means through which student learning is measured in the United States. Numerous studies have ascertained that traditional supplemental digital resources, such as apps, websites, videos, and software, are effective tools to enhance student performance with mathematics (e.g., Boster et al, 2007;Foster, Anthony, Clements, Sarama, & Williams, 2016;Kiriakidis & Geer, 2014;Securro, Jones, Cantrell, & Blackwell, 2006). While these studies have presented research-based findings to substantiate the positive effects associated with the use of supplemental digital resources during math instruction, the literature has also pointed to possible disadvantages.…”
Section: Impact Of a Web-based Adaptive Supplemental Digital Resourcementioning
confidence: 99%
“…Recently, only a few CAI intervention studies have focused on the early numeracy skills of young children (i.e. before the beginning of formal schooling) with mathematical learning difficulties (Baroody et al 2012;Foster et al 2016;Praet and Desoete 2014;Räsänen et al 2009;Salminen et al 2015a;Salminen et al 2015b;Schacter et al 2016b;Schacter and Jo 2016a;Wilson et al 2009). These studies (see supplementary material for detailed description) have primarily reported improved numeracy skills, at least in one of the measured numeracy skills, in the samples of children with low early numeracy skills.…”
Section: Computer-assisted Instruction (Cai) In Mathematicsmentioning
confidence: 99%
“…In order to support early numeracy learning in low-performing children, educational games should have a good research-based structure (Aunio and Räsänen 2015), so that the most essential skills are practiced enough and so that tasks follow one another in a developmentally valid order (Foster et al 2016). In addition, effective mathematics educational games have been found to include specific instructional elements that are considered beneficial for low-performing children's learning, such as explicit and structured instruction (Seo and Bryant 2009).…”
Section: Low-performing Children Need Extensive Explicit and Structurmentioning
confidence: 99%